2018
DOI: 10.1002/lary.27080
|View full text |Cite
|
Sign up to set email alerts
|

The survival impact of surgical therapy in squamous cell carcinoma of the hard palate

Abstract: 4. Laryngoscope, 128:2050-2055, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…To our knowledge, only two studies have examined the independent prognostic factors for survival in specific subsites of the oral cavity ( 15 , 16 ). In a study that described the incidence and determinants of survival of 1,489 patients with SCC of the hard palate between 1973 and 2014 using the SEER database, Alonso et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only two studies have examined the independent prognostic factors for survival in specific subsites of the oral cavity ( 15 , 16 ). In a study that described the incidence and determinants of survival of 1,489 patients with SCC of the hard palate between 1973 and 2014 using the SEER database, Alonso et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a study that described the incidence and determinants of survival of 1,489 patients with SCC of the hard palate between 1973 and 2014 using the SEER database, Alonso et al . found that advanced age, nonoperative treatment, radiation therapy, tumor stage and grade were independently associated with worse overall survival ( 15 ). In the current study, in addition to tumor stage, male gender and low education level were also independently associated with poor survival in patients with SCC of the hard palate.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery of hard palate cancer frequently does not include removal of the underlying bone [129]. However, management guidelines specifically pertaining to hard palate cancer are based on expert opinion owing to scant evidence [130]. Enucleation is avoided for hard palate cancer because it is associated with a high risk of recurrence whether enucleation is safe for hard palate cancer remains unknown [131].…”
Section: Guidelines For Surgical Treatment Of Oral Cancermentioning
confidence: 99%
“…Patients with early-stage squamous cell carcinoma (ESCC; TNM I and II) survive longer than those with advanced-stage squamous cell carcinoma (ASCC; TNM III and IV), with survival rates of 64.2 and 30.1% for early and late stages, respectively (4). Despite improvements in treatment modalities, the 5-year overall survival rate has improved only marginally, with 33% of cases surviving between 1973 and 2014, compared with 41% between 2006-2011 (5,6). Delayed diagnosis and the lack of accurate and timely treatment, derived from the bias of the standards of clinical decision-making based on the clinical experience and subjective judgment of doctors, are considered to be the major reasons for the poor prognosis.…”
Section: Introductionmentioning
confidence: 99%